Psikologi Komunikasi Remaja Terhadap Konsep Diri di Kalangan Komunitas Cosplayer Medan - Abdurrahman Fadhiil Pinem (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2018)
Cosplay otaku is a person who has obsessions for the art of appearance with wearing costumes and accessories that imitates public figures of character better than the comic figure and cartoons that originating in the country of japan. The state of being a cosplayer otaku-cosplay obsessed closely related to how the concept of himself formed. It is not uncommon in doing cosplay the cosplayer deprive of the character native himself and had been replaced by a figure by which they perankan character. In relation to this matter, writer interested to scrutinize how self-concept otaku cosplay among community cosplayer Medan. This study aims to to see how mind, self, and society said in build self-concept cosplayer in Medan. The use writers interaksionisme theory symbolic belonging to george herbert said mead and qualitative research methods have descriptive. This research result indicates that self-concept otaku cosplay having self-concept positive where the otaku agents cosplay can develop potential which they have with bercosplay but also have the concept of soul that has negative where otaku cosplay not very open and lack of communication between significant other or on the community. Reference group does not change the otaku cosplay communiqu that is closed and a lack of their communication .